Perilous Memories : The Asia-Pacific War(s) - Yoneyama, Lisa, 1959-; White, Geoffrey M. (Geoffrey Miles), 1949-; Fujitani, Takashi (Book collections on Project MUSE., 2001)
A rethinking of the differing national memories of the Second World War in the Pacific in light of recent theories of nationalism, imperialism, and colonialism.